Communication in crisis management or crisis in the communications management: BP case and Gulf of México oil spill - Rivero Terry, Jose (2010)
In the first semester 2010, we learned abour the BP oil company crisis ocurred in the Gulf of Mexico Coast which attracted the world's an ention and concern because of irsextent and consequences as well as for the importance provided by the media. This situation made BP lose thousands of millions of dollars in a short time, not only because the company became directly responsible but also because of indirect repercussions generated by inadequate crisis management of executives, diiectors and consultantt.